Sports diplomacy sports in the diplomatic activities of states and non-state actors - Kobierecki, Michał Marcin (Lexington research in sports, politics, and international relations., 2020)
This book analyzes the place and role of sport within public diplomacy, including theoretical conceptualizations of the category of sports diplomacy as a sub-category of public diplomacy and empirical research of selected examples of the use of sport within public diplomacy. The empirical part of the book refers to three approaches to sports diplomacy and concerns the utilization of sport by states in order to shape relations with other states, the role of sport in building the international image of a state and the diplomatic subjectivity of international sports organizations. In reference to the first two approaches, the book uses comparative case study was in order to make observations and generalizations concerning sports diplomacy. Apart from that, the book includes a detailed study of the diplomatic subjectivity of the International Olympic Committee.